Intermediate energy Coulomb excitation as a probe of nuclear structure at radioactive beam facilities - Bertulani, C.A.; Stuchbery, A.E.; Mertzimekis, T. J.; Davies, A.D. (Phys. Rev. C, 2003)
The effects of retardation in the Coulomb excitation of radioactive nuclei in intermediate energy collisions (Elab ? 100 MeV/nucleon) are investigated. We show that the excitation cross sections of low-lying states in 11Be, 38,40,42S, and 44,46Ar projectiles incident on gold and lead targets are modified by as much as 20% due to these effects. The angular distributions of decaying ? rays are also appreciably modified.